Rumah Bugis sebagai Bentuk Pemertahanan Budaya Masyarakat Bugis di Desa Kemojan Karimunjawa - Titiek Suliyati (Endogami: Jurnal Ilmiah Kajian Antropologi, 2019)
This paper examines the Bugis house in the Kemojan Village of Karimunjawa as a form of cultural retention of the Bugis people. The efforts of the Bugis community of Kemojan Karimunjawa Village maintain the preservation of the Bugis house as their residence because they try to maintain their culture. Besides that they want to introduce to the people around them their identity through the philosophy contained in the construction of Bugis houses. Although the Bugis house in Kemojan Village is different from the Bugis house in South Sulawesi, but in principle the philosophy and concept of development are the same. The development of tourism which is rampant in Karimunjawa has caused Bugis people in Kemojan Village to take the initiative to build several Bugis houses on the beach for Home Stay. Home Stay was built in accordance with the rules and forms of Bugis houses in Sulawesi. With the existence of Bugis houses for the sake of this tourism, it is hoped that the public will get to know the Bugis culture overseas